Modelos de elección discreta: una aplicación a la demanda por cupos universitarios en Colombia. (2009)
This article makes a quantitative characterization of high school graduates from intermediate cities and their demand for university places. Specifically speaking, the results show that the number of programs offered by universities increases the probability of choosing the latter,whereas university ranking has an inverse relationship with that probability. On the other hand, the socio-economic state of high school graduates measured by their “estrato” is a variable that explains their choice of university. Specifically, the students from low and middle estratos show a strong trend in terms of choosing public universities, whereas those from high estratos prefer private universities.